2010
DOI: 10.4236/abb.2010.14043
|View full text |Cite
|
Sign up to set email alerts
|

Sponge-associated bacteria of Lakshadweep coral reefs, India: resource for extracellular hydrolytic enzymes

Abstract: Sponges (Phylum: Porifera) is one of the major groups in the Lakshadweep coral reefs. These sponges harbor diverse bacteria with metabolic potentiality. From biodiversity to biotechnological prospecting, scientific investigations related to sponge associated microorganisms have expanded, but remain rather limited to few geographic locations. In this study, culturable bacteria associated with two demosponges viz Dysidea granulosa, Sigmadocia fibulata and the ambient water were screened for commercially importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The presence of bacteria producing enzymes in sponges was reported early by some authors (Mohapatra et al 2003, Feby andNair 2010). These enzymes have an important role in helping sponges nutrition hydrolyzing complex molecules present in marine environment that sponges cannot directly absorb (Marx et al 2007).…”
Section: Enzymatic Testsmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of bacteria producing enzymes in sponges was reported early by some authors (Mohapatra et al 2003, Feby andNair 2010). These enzymes have an important role in helping sponges nutrition hydrolyzing complex molecules present in marine environment that sponges cannot directly absorb (Marx et al 2007).…”
Section: Enzymatic Testsmentioning
confidence: 90%
“…Mohapatra et al (2003) and Feby and Nair (2010) found amylase as one of the most predominant enzyme produced by bacteria associated to sponges. Our results do not corroborate these data.…”
Section: Enzymatic Testsmentioning
confidence: 99%
“…In some reports, it has been explained that marine sponges are filter feeders which allows the microbes to enter inside the body from the surroundings and these may result in the accumulation of many secondary metabolites of microbial origin [8][9][10]. It has been estimated that nearly 40% of sponge tissue volume contains associated microbes, with the population of 10 9 microbial cells per mL of sponge tissue, which is quite large numbers when compared to seawater density [11,12]. Many microorganisms have been associated with sponges, but very limited studies have been carried out in Indian coastal waters, that too particularly about marine Streptomyces [13].…”
Section: A Rt I C L E I N F O Abstractmentioning
confidence: 99%
“…Symbiotic bacteria associated with marine sponges have been proposed as the actual producers of these bioactive compounds (Uria & Piel, 2009). Recently, a number of hydrolytic enzymes have been reported to be secreted by sponge-associated bacteria, exemplified by amylase, protease, deoxyribonuclease, gelatinase, lipase, phosphate, urease (Feby & Nair, 2010), chitosanase (Chasanah et al, 2009), andChitinase (2005). Such extracellular hydrolytic enzymes may mediate the metabolism of complex organic matters, thereby assisting the host in nutrition and various metabolic processes (Marx et al, 2007).…”
Section: Introductionmentioning
confidence: 99%